# trigonometry

posted by .

can i use factoring to simplify this trig identity?
the problem is sinx + cotx * cosx i know the answer is cscx and i know how to get it but i want to know if i can do factoring to get it bc i tried to but it wont give me the answer .
this is the step i went through:
1) sinx + cotx * cosx turns into sinx +(cosx/sinx)*cosx
2) i try to factor out sinx so that i would get sinx(1+ cosx * cosx)
3) that left me with sinx(1+cos^(2) x) that's where i im lost can anyone enlighten me plz

• trigonometry -

cot = cos/sin, so you have

sin + cos^2/sin
= (sin^2+cos^2)/sin
= 1/sin
= csc

• trigonometry -

im well aware of that steve thank you for answering but i really wanted to know was is it at all possible to use factoring to solve this like i have up there

• trigonometry -

I don't see any way to use factoring. You don't in fact come up with

sin(1+cos^2)

because you have that pesky 1/sin under the cos^2.

If you try to fractor out the sin, you get

sin(1+cos^2/sin^2)

and again you end up with sin^2+cos^2 on top.

• trigonometry -

We could do some " silly" factoring

sinx + (cosx/sinx)(cosx)
= sinx + cos^2 x (sinx)^-1
= (sinx)^-1 (sin^2 x + cos^2 x)
= (sinx)^-1
= 1/sinx
= cscx

## Similar Questions

1. ### Math

Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant help you (cscX-cotX)=1/sinX - cosX/sinX = (1-cosX)/sinX If you square this you have (1-cosX)^2/(sinX)^2 Now use (sinX)^2 = 1 - (cosX)^2 to get (1-cosX)^2 / 1 - …
2. ### trig

express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is that right?
3. ### Trigonometry.

( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! Generally these are done by changing everything to sines and cosines, unless you see some obvious identities. Also generally, it is best to start with the more complicated side …
4. ### Pre-calc

prove the identity: (cosx)(tanx + sinx cotx)=sinx+cos(squared)x i need steps to show how i got the answer generally, it is a good idea to change all trig ratios to sines and cosines, and start with the more complicated-looking side. …
5. ### drwls

My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) = (sinx/cosx)*cotx*(1/sinx) "The last steps should be obvious" Not to me. I can convert (sinx/cosx) to …
6. ### Math 12

Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+cosx = cscxtanx/sinx+cosx Is the correct answer cscxtanx/sinx+cosx?
7. ### Trigonometry

Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+cosx = cscxtanx/sinx+cosx Is the correct answer cscxtanx/sinx+cosx?
8. ### Math

Im really struggling with these proving identities problems can somebody please show me how to do these?
9. ### Math

I'm only aloud to manipulate one side of the problem and the end result has to match the other side of the equation Problem 1. sinx + cosx + sinx + tanx + cosxcotx = secx + cscx Problem 2. ((sinx + cosx)/(1 + tanx))^2 + ((sinx - cos^2x)/(1 …
10. ### Precalculus/Trig

I can't seem to prove these trig identities and would really appreciate help: 1. cosx + 1/sin^3x = cscx/1 - cosx I changed the 1: cosx/sin^3x + sin^3x/sin^3x = cscx/1-cosx Simplified: cosx + sin^3x/sin^3x = cscx/1-cosx I don't know …

More Similar Questions